'Royal Gala' apple quality stored under ultralow oxygen concentration and low temperature conditions - Weber, Anderson; Brackmann, Auri; Anese, Rogério de Oliveira; Both, Vanderlei; Pavanello, Elizandra Pivotto (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the interaction of ultralow oxygen concentrations (ULO) with storage temperatures and carbon dioxide partial pressures and its influence on fruit quality preservation and on the occurrence of physiological disorders in 'Royal Gala' apples. The experiment was carried out in a completely randomized design, with four replicates 25-fruit. ULO conditions (1.0 kPa O2 + 2.0 kPa CO2; 0.8 kPa O2 + 1.5 kPa CO2; 0.8 kPa O2 + 1.0 kPa CO2; 0.6 kPa O2 + 1.5 kPa CO2; and 0.6 kPa O2 + 1.0 kPa CO2) were tested at 0, 0.5 and 1.0°C, in a 5x3 factorial arrangement. Fruit quality and ripening analyses were performed after eight-month storage plus seven days of shelf-life at 20°C. Oxygen partial pressures below 0.8 kPa increased the occurrence of internal breakdown and mealiness. The best ULO condition was 1.0 kPa O2 + plus 2.0 kPa CO2 at 1.0°C. The interaction of ULO conditions and storage temperatures shows the need of increasing O2 partial pressure at higher storage temperatures.